Comparison of conservative management and renal replacement therapy in the Elderly with CKD stage 5. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hussain, Jamilla; Russon, Lynne; Mooney, Andrew
Abstract : Background: There is limited data on the outcomes of older patients with chronic kidney disease (CKD) stage 5 undergoing renal replacement therapies (RRT) or conservative management (CM). Aims: Through conducting the largest study in patients over 70 years old we aimed to establish key factors influencing survival and quality of life of patients who chose either RRT or CM at CKD stage 5. This information is essential to ensure patients and professionals can make informed decisions regarding management in such complex cases. Methods: A retrospective observational survival study comparing both groups was conducted. Results: 441 patients were included (172 CM, 269 RRT). The RRT group survived for longer when survival was taken from the time GFR <20 ml/min (p<0.001). This remained the case when survival was calculated from GFR 15ml/min (p=0.02) and 12 ml/min (p=0.02). However when stratified for age (greater than 80 years old), Charlson comorbidity score (greater than 8) and WHO performance score (greater than 2) RRT no longer had a statistically significant survival advantage. In terms of quality of life, the RR of an acute hospital admission comparing RRT to CM was 1.6, p<0.05, 95% CI (1.14 to 2.13). 47% of CM patients died in hospital, in comparison the Renal Registry states 69% of RRT patients die in hospital. The CM group also had greater access to specialist palliative care (SPC) resources. 131 CM patients accessed community SPC services versus 0 RRT patients. 85% of CM patients had a SPC consultant review versus 4% of RRT patients. Conclusion: For patients over 80 years old, with high comorbidity scores and low performance status RRT did not offer a survival advantage over CM. Additionally, through accessing a dedicated CM pathway patients have greater access to SPC services and are less likely to be acutely admitted to or die in hospital.